(untitled) (BIS Humanities and Social Science, 2026)
This research is motivated by changing digital trends that require brands to adapt their communication strategies to younger generations who are increasingly selective about marketing messages. Branlight, as a creative agency, plays a role in managing internal communications so that the external strategies produced are relevant and effective in reaching digital audiences. To understand and analyze the internal communication process at Branlight in formulating client brand communication strategies that are acceptable to different generations, this study uses a descriptive qualitative research method with data collection techniques through in-depth interviews. Data analysis was conducted descriptively with reference to the POAC communication management theory, where each stage emphasized understanding the communication process systematically. This study focuses on determining how Branlight Creative communication strategy builds the brand identity of clients across generations. The results of the study show that coordinated internal communication between the strategy, creative, and content teams plays an important role in producing consistent client brand messages. Previous studies have emphasized external communication, while this research contributes by highlighting the role of internal agency communication in building cross-generational brand identity. The trend research process and internal discussions form the basis for Branlight Creative in formulating external communication strategies that are relevant to across generations.